Histórias em quadrinhos no incentivo à leitura: um estudo de caso na Escola Alzira Pernambuco - SILVA, Franciane Silva da (2018)
Encouraging reading needs to be cultivated from the very beginning of the human being, as it can be a great way to work on an imagination, creativity, writing and vocabulary. In this way, the pleasure of reading is also a source of knowledge. Thus, a present research aims to show how comics and a resource to arouse pleasure by reading. In addition, in the work is shown how a comic book helps in the development of reading and writing, in addition to reporting the performance of the students 6th year of the Alzira Pernambuco school, in activities with the use of comics. The methodological approach used in the design of a bibliographic research, where authors such as Abreu (2008), Assis (2010), Bari (2008) and among other authors who were essential in the research were consulted, in addition, a field research with Students teachers of the Alzira Pernambuco School of the sixth grade.